2021
DOI: 10.1055/s-0041-1735938
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Problems Experienced by Patients with Bowel Endometriosis Awaiting Surgery

Abstract: Objective To assess the most common psychological disturbances in women with deep endometriosis and bowel involvement who are waiting surgical treatment and to evaluate what forms of coping are used to solve the problem. Methods This was a cross-sectional observational study of 40 women diagnosed with deep endometriosis and intestinal symptoms. They completed two questionnaires: one for anxiety and depression (Hospital Anxiety and Depression Scale [ HADS]) and the Scale of Mode of Confronting Problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Each of the studies included in the review reported a high rate of prevalence of depressive and anxiety symptoms in women with endometriosis. Ribeiro et al ( 25 ) reported that 77.1% of patients exhibited anxiety and depression simultaneously, indicating a high rate of comorbidity in women with endometriosis. In addition, it was reported that patients with endometriosis had an increased risk of developing clinically recognized depression and anxiety compared with women never diagnosed with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the studies included in the review reported a high rate of prevalence of depressive and anxiety symptoms in women with endometriosis. Ribeiro et al ( 25 ) reported that 77.1% of patients exhibited anxiety and depression simultaneously, indicating a high rate of comorbidity in women with endometriosis. In addition, it was reported that patients with endometriosis had an increased risk of developing clinically recognized depression and anxiety compared with women never diagnosed with endometriosis.…”
Section: Discussionmentioning
confidence: 99%